Abscisic acid activation of oleosin gene HvOle3 expression prevents the coalescence of protein storage vacuoles in barley aleurone cells. (26th October 2021) - Lee, Sung-eun; Yoon, In Sun; Hwang, Yong-sic
Abstract: Protein storage vacuoles (PSVs) in aleurone cells coalesce during germination, and this process is highly coupled with mobilization of PSV reserves, allowing de novo synthesis of various hydrolases in aleurone cells for endosperm degradation. Here we show that in barley ( Hordeum vulgare L.) oleosins, the major integral proteins of oleosomes are encoded by four genes ( HvOle1 to 4 ), and the expression of HvOle1 and HvOle3 is strongly up-regulated by abscisic acid (ABA), which shows antagonism to gibberellic acid. In aleurone cells, all HvOLEs were subcellularly targeted to the tonoplast of PSVs. Gain-of-function analyses revealed that HvOLE3 effectively delayed PSV coalescence, whereas HvOLE1 only had a moderate effect, with no notable effect of HvOLE2 and 4. With regard to longevity, HvOLE3 chiefly outperformed other HvOLEs, followed by HvOLE1. Experiments swapping the N- and C-terminal domain between HvOLE3 and other HvOLEs showed that the N-terminal region of HvOLE3 is mainly responsible, with some positive effect by the C-terminal region, for mediating the specific preventive effect of HvOLE3 on PSV coalescence. Three ACGT-core elements and the RY-motif were responsible for ABA induction of HvOle3 promoter activity. Transient expression assays using aleurone protoplasts demonstrated that transcriptional activation of the HvOle3 promoter was mediated by transcription factors HvABI3 and HvABI5, which acted downstream of protein kinase HvPKABA1.